2018
DOI: 10.1002/agr.21577
|View full text |Cite
|
Sign up to set email alerts
|

Good agricultural practices, farm performance, and input usage by smallholders: Empirical evidence from Nepal

Abstract: This study examines the impact of good agricultural practices (GAP) on the farm income and fertilizer usage of smallholders in Nepal. Using qualitative variables, we first construct a GAPindex, a measure of the intensity of GAP adoption. The findings show that a GAP-index constructed through principal component analysis performs better than a GAP-index constructed with Markowitz's portfolio method. Results reveal a positive and significant relationship between the GAP-index and farm income and a negative and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The second pathway reveals that OSA adoption can influence net returns by affecting production costs. OSA adoption in crop production is expected to substitute or complement chemical fertiliser (Hassen, 2018; Bairagi et al ., 2019), and thereby, it may affect production costs either positively or negatively. Specifically, if organic soil amendments are applied as complements to chemical fertiliser, OSA adoption tends to increase production costs.…”
Section: Analytical Framework and Empirical Strategymentioning
confidence: 99%
“…The second pathway reveals that OSA adoption can influence net returns by affecting production costs. OSA adoption in crop production is expected to substitute or complement chemical fertiliser (Hassen, 2018; Bairagi et al ., 2019), and thereby, it may affect production costs either positively or negatively. Specifically, if organic soil amendments are applied as complements to chemical fertiliser, OSA adoption tends to increase production costs.…”
Section: Analytical Framework and Empirical Strategymentioning
confidence: 99%
“…The GAP is a set of principles that apply to the farm production and post-production processes to produce safe and healthy food and non-food agriculture products, considering economic, social, and environmental sustainability (Hobbs 2003). A recent study conducted by Bairagi et al (2019) found that the adoption of GAP could increase farm income by 6.2% and decrease the use of synthetic fertilizers by 31% for rice, lentil, tomato, and ginger in Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three distinct agro-ecological zones of the country, food insecurity is most pronounced in the mid-hill and mountain regions (Karki et al 2015). Low agricultural productivity due to the low adoption of modern production technologies has been identified as the primary reason for food insecurity and high poverty in the region (Bairagi, Mishra, and Giri 2019;Ghimire and Huang 2015). The adoption of technologies, such as hybrid maize, has the potential to improve food security and reduce rural poverty in Nepal by increasing crop productivity and profitability.…”
Section: Resource Constraints and The History Of Hybrid Maize Dissemi...mentioning
confidence: 99%